COFDM System: An Overview - Mhnd Farhan (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2023)
This article compares the performance of two modulation techniques—quadrature phase shift keying (QPSK) and M-ary quadrature amplitude modulation (M-QAM) with M=8, 16, 32, and 64—in a coded orthogonal frequency division multiplexing system. As an error-correcting code, convolutional technology is employed. A vehicular channel with additive white gaussian noise (AWGN) is utilized for communication. According to simulation data, for QPSK and M-QAM, a coded orthogonal frequency division multiplexing system performs better than an uncoded one. Additionally, the system performs better with QPSK than it does with M-QAM. Additionally, when M rises, the performance declines.